The Motif of Palingenesis in the Megatext of World War I - Molchanova, Diana (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
The paper explores poems by Russian and Belarusian authors written during World War I and directly related to this historical phenomenon. The presence of a common “mission” – that of overcoming death and destruction – induces the author to combine these texts into a megatext. Problems related to the creation and existence of supertext formations have become a priority of research in modern literary studies. The range of such polytextual unities is gradually expanding and has been acquiring a tradition of scholarly description. In this regard, the question of whether to consider the text(s) of World War I as a megatext is a legitimate one and requires an answer. A megatext ought to be understood as a synthetic supersaturated text that preserves traces of an “extra-textual substrate”. The megatext of World War I, from our point of view, is a complex semiotic formation of a mythopoetic nature. An analysis of the poetry of this period (1914–1915) reveals a similarity between the texts of authors that belong to different literary trends and schools as well as to different national literatures. This similarity can be explained by the influence of a common “mission”, and this is why the poems reproduce the same model of the world. This model of the world can be investigated through motives; among them the author of the paper indicates images of fire, including the world conflagration, in combination with images of food. The unifying principle behind these images can be identified as the motif of palingenesis, which indicates the substrate mythologem of rebirth or resurrection. The peculiarity of “life-and-death” issue in the megatext of the World War I is that the “eternal return” and rebirth lead not to a renewal, but to a circular movement between deaths: after dying in the universal conflagration, the world is not reborn, as could be expected. Cyclical by its nature, the mythological plot finds its realisation in this megatext in the form of a cumulative chain.